Workplace performance, worker commitment and loyalty - Sarah Brown; Jolian McHardy; Robert McNabb; Karl Taylor (Institute for the Study of Labor (IZA), 2011)
Using matched employer-employee level data drawn from the 2004 UK Workplace and Employee Relations Survey, we explore the determinants of a measure of worker commitment and loyalty (CLI) and whether CLI influences workplace performance. Factors influencing employee commitment and loyalty include age and gender, whilst workplace level characteristics of importance include human resource practices. With respect to the effects of employee commitment and loyalty upon the workplace, higher CLI is associated with enhanced workplace performance. Our findings that workplace human resources influence CLI suggest that employers may be able to exert some influence over the commitment and loyalty of its workforce, which, in turn, may affect workplace performance.
urn:nbn:de:101:1-201104113200
Keywords: J20; J50; 330; commitment; financial performance; labor productivity; loyalty; Leistungsmotivation; Arbeitsproduktivität; Mitarbeiterbindung; Arbeitszufriedenheit; Großbritannien